Strengthening single-bolt timber joints with externally bonded CFRP composites. (December 2020) - Yang, Jia-Qi; Smith, Scott T.; Wu, Yu-Fei; Feng, Peng
Abstract: Dowel type timber joints are popular in timber construction and they can be used in timber trusses and moment resisting frames (i.e. beam-to-column joints). Bearing strength is an important design parameter that influences the strength of each failure mode a joint can experience. Therefore, in order to enhance the load carrying capacity of dowel-type joints, the bearing strength of the timber should be increased. Externally bonded fibre-reinforced polymer (FRP) composites offer effective and rapid retrofit and repair solutions for the joints. As a result, this paper reports a series of tests on fifty single-bolt timbers joints subjected to tension of which 25 joints were made from softwood and 25 from hardwood. Forty of the joints were strengthened with four different arrangements of externally bonded carbon FRP plates representing fibre orientations of 0°, 0°/90°, ±45°and ± 30°to the grain direction. In addition, ten joints served as unstrengthened controls. The test details as well as failure modes, strength and ductility of all test joints are reported in addition to joint strength predictions. Overall, the strengthening schemes adopted were found to enhance the strength of the timber joints although their effectiveness varied. With proper fibre orientation, the strength of the joint was observed to increase by 50% above the control joint. The FRP was also found in cases to alleviate brittle timber failure by preventing premature splitting of the timber.